2012
DOI: 10.1136/sextrans-2012-050594
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1 cosmopolitan and HTLV-2 subtype b among pregnant women of non-endemic areas of Argentina

Abstract: HTLV-1/2, which have been associated with different diseases, are circulating among PW of Argentina, even in non-endemic areas. Therefore, testing should be recommended in women who have risk factors for these infections given that the majority of HTLV-1/2 mother to child transmission can be prevented by the avoidance of breast feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
1
7
1
Order By: Relevance
“…Previous studies in high-endemic areas of Brazil and Africa have reported prevalence rates similar to values found in this study [2, 28], corroborating that Jujuy province is a high endemic area for HTLV-1 infection, with prevalence rates much higher than values recognized in other regions of the country [2931]. In other high-endemic areas of the world, such as Japan, the prevalence of HTLV-1 is 38.5% among relatives of infected individuals [32].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in high-endemic areas of Brazil and Africa have reported prevalence rates similar to values found in this study [2, 28], corroborating that Jujuy province is a high endemic area for HTLV-1 infection, with prevalence rates much higher than values recognized in other regions of the country [2931]. In other high-endemic areas of the world, such as Japan, the prevalence of HTLV-1 is 38.5% among relatives of infected individuals [32].…”
Section: Discussionsupporting
confidence: 90%
“…An international study that analyzed Indians from Colombia, Venezuela, Bolivia, Brazil, Paraguay and Chile found HTLV-2 positivity of up to 57.9% in the Kayapo, Brazil, 34.8% in Alacalf, Chile and 16.4% in the Chaco, Paraguay [437]. Higher HTLV-2 positivity has also been demonstrated for Amerindians populations from Argentina, such as the Toba (10-36.4%), Gran Chaco (22%), Mataco (3%) and Mapuches (2%) [284,290,[385][386][387]412,437,[440][441][442][443]. Other Amerindians that exhibited an almost exclusive HTLV-2 prevalence were those from the Gran Chaco region of Paraguay (4-44%) [355,442], Boca Colorado (4.54%) and Galilea (2.38%) in Peru [443] and the Yaruro/Guahibo (24.8-61%) and the Pume (5%) in Venezuela [444][445][446].…”
Section: Htlv Prevalence and Morbidity In Latin Americamentioning
confidence: 93%
“…HTLV prevalence in central provinces ranged from 0% to 0.2% (0.028-0.26% HTLV-1; 0.007-0.03% HTLV-2) [281,282,284,285,[287][288][289][290][291][292][294][295][296]384]. In contrast, this incidence is increased up to 9.8% of HTLV-1 in Jujuy [280,292,385,386], and to 31.5% when Jujuy family clusters were studied [387]. Surprisingly, other Northern Argentinean cities reported low HTLV positivity, namely 0.16-0.7% in Salta that borders with Jujuy [284,292], 0.6% in Formosa [292] and 0.007% in Misiones [295].…”
Section: Htlv Prevalence and Morbidity In Latin Americamentioning
confidence: 99%
“…It causes an aggressive malignancy known as ATLL and a progressive chronic inflammatory neurological disease named HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) that is progressively invalidating (14). In this case, sexual transmission from her husband was confirmed, who got infected from her mother who died of ATLL years before in a non-endemic area of Argentina (15). So, physicians should bear HTLV-1 infection in mind and suspect it regardless of the patient’s residence.…”
Section: Background and Discussionmentioning
confidence: 70%